Pediatric heart‐lung transplantation: A contemporary analysis of outcomes. (17th February 2020) - Riggs, Kyle W.; Chapman, Jacquelyn L.; Schecter, Marc; Towe, Christopher; Zafar, Farhan; Morales, David L. S.
Abstract: Background: Pediatric heart‐lung transplantation (HLT) is rare, and no report has analyzed patient outcomes since time of listing. We analyzed pediatric HLTs to understand risk factors for waitlist and post‐HLT mortality. Methods: All pediatric (<18 year old) HLT candidates were identified within the UNOS database (n = 573) and grouped by age, era, and by diagnosis. Logistical regression and Cox proportional hazard modeling identified risk factors for 6‐month WL and overall post‐transplant mortality. Results: 209/573 (37%) HLT candidates were transplanted, 7% recovered, 42% died waiting, and 15% were removed for another/unknown reason. Diagnoses were primary pulmonary hypertension(n = 130), congenital heart disease(CHD) without Eisenmenger's syndrome (ES) (n = 65), CHD with ES (n = 73), and other (n = 305). Patients with a diagnosis other than CHD with ES (OR: 7.55, P = .001), on IV inotropic support (OR: 2.79, P < .001), and infants (OR: 2.20, P = .004) were associated with waitlist mortality. There has been a 56% reduction in HLTs across eras (Era 1:10.8/yr vs Era 2:4.7/yr). Risk factors for post‐transplant mortality were ECMO (HR: 4.1, P = .016), and being infant (HR: 2.2, P = .04) or 1‐11 years old (HR: 1.78, P = .015). ECMO patients have an 87% 2‐year mortality rate with a median post‐transplant survival of 64 days. Overall, post‐transplant survival was unchanged (log‐rank P = .067) between eras. Excluding ECMO patients, in the recent era 29 non‐infant patients with primary pulmonary hypertension had 93% 1‐year survival and 67% 5‐year survival. Conclusions: Nearly 600 pediatric patients have been listed for HLT in UNOS, although numbers are decreasing in the current era. HLT for a patient on ECMO appears to be an ineffective strategy; however, in well‐selected cohorts, HLT can provide considerable post‐transplant survival.